From isolation to cross-cultural collaboration: My international PhD journey as tauiwi - Amrit Melissa Dencer-Brown (University of Johannesburg, 2020)
This reflective piece is about my journey as an international PhD candidate from the UK to Aotearoa (New Zealand). I speak about my search to try and find a sense of belonging as an outsider and some of the challenges in doing community-focused research as an early career researcher from elsewhere. This piece includes key challenges of building networks, collaboration and overcoming the death of my father, half-way through my PhD. I speak about a toolkit of strength and resilience I had to create and now use in the support of my students and peers as a lecturer in education during the pandemic. This piece is about finding kindness and compassion in myself and receiving it from others to help with isolation in difficult times.   Keywords: Reflection, Resilience, Compassion, Kindness, Networks, Community, Isolation How to cite this article: Dencer-Brown, A.M. 2020. From isolation to cross-cultural collaboration: My international PhD journey as tÅ iwi. Scholarship of Teaching and Learning in the South. 4(2): 228-234. https://doi.org/10.36615/sotls.v4i2.142. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/